Chapter Il ruolo del contatto nell'aspetto perfettivo in griko: forme sintetiche ed analitiche in competizione - Ledgeway, Adam (Biblioteca di Studi Slavistici, 2023)
The aim of this article is to discuss a change in the expression of perfective aspect in Griko. According to Rohlfs (1977), this variety of Italo-Greek only possesses a synthetic past perfective form, thus failing to mark a distinction between the past punctual and present perfect values of the perfective. And yet, some changes in the expression of this macrocategory were already taking place at the time of Rohlfs when an originally resultative periphrastic form was beginning to be used beyond its original limits. By taking into account a wider array of sources, including both early and contemporary written attestations, as well as data collected with native speakers, we show how the regrammaticalization of this analytic construction, from resultative to present perfect marker, was already under way in the late nineteenth century and is now completed for some speakers. The article concludes with a number of reflections about the role played by contact in these developments.